Significance of Microscopically Incomplete Resection Margin After Esophagectomy for Esophageal Cancer. Issue 4 (April 2016) - Markar, Sheraz R.; Gronnier, Caroline; Duhamel, Alain; Pasquer, Arnaud; Théreaux, Jérémie; Rieu, Mael Chalret du; Lefevre, Jérémie H.; Turner, Kathleen; Luc, Guillaume; Mariette, Christophe
Abstract : Objective: The objectives of this study were to establish if R1 resection margin after esophagectomy was (i) a poor prognostic factor independent of patient and tumor characteristics, (ii) a marker of tumor aggressiveness and (iii) to look at the impact of adjuvant treatment in this subpopulation. Methods: Data were collected from 30 European centers from 2000 to 2010. Patients with an R1 resection margin (n = 242) were compared with those with an R0 margin (n = 2573) in terms of short- and long-term outcomes. Propensity score matching and multivariable analyses were used to compensate for differences in baseline characteristics. Results: Independent factors significantly associated with an R1 resection margin included an upper third esophageal tumor location, preoperative malnutrition, and pathological stage III. There were significant differences between the groups in postoperative histology, with an increase in pathological stage III and TRG 4–5 in the R1 group. Total average lymph node harvests were similar between the groups; however, there was an increase in the number of positive lymph nodes seen in the R1 group. Propensity matched analysis confirmed that R1 resection margin was significantly associated with reduced overall survival and increased overall, locoregional, and mixed tumor recurrence. Similar observations were seen in the subgroup that received neoadjuvant chemoradiation. In R1 patients adjuvant therapy improved survival and reduced distant recurrence however failed to affect locoregional recurrence. Conclusions: This large multicenter European study provides evidence to support the notion that R1 resection margin is a prognostic indication of aggressive tumor biology with a poor long-term prognosis.